Epilepsy and nodding syndrome in association with an Onchocerca volvulus infection drive distinct immune profile patterns - Arndts, Kathrin; Kegele, Josua; Massarani, Alain S.; Ritter, Manuel; Wagner, Thomas; Pfarr, Kenneth; Lämmer, Christine; Dörmann, Peter; Peisker, Helga; Menche, Dirk; Al-Bahra, Mazen; Costa, Clarissa Prazeres da; et al. (PLoS neglected tropical diseases, 2023)
Previous studies have described the association of onchocerciasis (caused by Onchocerca volvulus) with epilepsy, including nodding syndrome, although a clear etiological link is still missing. Cases are found in different African countries (Tanzania, South Sudan, Uganda, Democratic Republic of the Congo, Central African Republic and Cameroon). In our study we investigated immunological parameters (cytokine, chemokine, immunoglobulin levels) in individuals from the Mahenge area, Tanzania, presenting with either epilepsy or nodding syndrome with or without O. volvulus infection and compared them to O. volvulus negative individuals from the same endemic area lacking neurological disorders. Additionally, cell differentiation was performed using blood smears and systemic levels of neurodegeneration markers, leiomodin-1 and N-acetyltyramine-O, β-glucuronide (NATOG) were determined. Our findings revealed that cytokines, most chemokines and neurodegeneration markers were comparable between both groups presenting with epilepsy or nodding syndrome. However, we observed elevated eosinophil percentages within the O. volvulus positive epilepsy/nodding syndrome patients accompanied with increased eosinophilic cationic protein (ECP) and antigen-specific IgG levels in comparison to those without an O. volvulus infection. Furthermore, highest levels of NATOG were found in O. volvulus positive nodding syndrome patients. These findings highlight that the detection of distinct biomarkers might be useful for a differential diagnosis of epilepsy and nodding syndrome in O. volvulus endemic areas. Trial-registration: NCT03653975.
Gesehen am 07.02.2024